Simbolisme Kakereb Barong Dan Rangda Dalam Upacara Butha Yadnya Di Desa Bitra Gianyar - Yudha Triguna, Ida Bagus Gde; Bagiarta, I Nyoman Kembar; Sudanta, I Nyoman (Jurnal Penelitian Agama Hindu, 2025)
Kakereb is the veil used for Barong and Rangda, made from a square piece of white cloth measuring 1.2 meters by 1.2 meters. Its uniqueness lies in the sacred inscriptions (rerajahan) written on its surface. These inscriptions contain texts that represent a sacred symbolic system of Shaivite Tantric theology, encompassing the concept of Acintya (the inconceivable aspect of God) as well as sacred characters such as Ongkara and wijaksara. In addition to the textual elements, the kakereb also features symbolic images such as dragons, fire, weapons of the Dewata Nawasanga, and modre letters. The essential meaning behind the kakereb is that God (Shiva) is the essence that is both One and many (Eka-aneka). The One Supreme God (Eka), by His own will, manifests Himself into various deities and even into all that exists (sarwa). The kakereb, in relation to Barong and Rangda, symbolizes a theology of duality. God is glorified with the names Bhatara Shiva and Dewi Uma, who are considered the source, existence, and ultimate purpose of all things in the world. Shiva has a thousand names (sahasra nama), and so does Uma, illustrating the infinite aspects of their divinity. Thus, Balinese Hindus who follow the Shaivite Tantric tradition are not worshipping demons, but are in fact worshipping God through sacred and religious-magical forms such as Barong and Rangda. Although these figures may appear demonic on the surface, they are actually sacred embodiments known as Ratu Bagus and Ratu Ayu.